Elevated Fab glycosylation of anti-hinge antibodies. (2nd January 2023) - Koers, J; Derksen, NIL; Falkenburg, WJJ; Ooijevaar-de Heer, P; Nurmohamed, MT; Wolbink, GJ; Rispens, T
Abstract : Objective: Rheumatoid arthritis (RA) is characterized by systemic inflammation and the presence of anti-citrullinated protein antibodies (ACPAs), which contain remarkably high levels of Fab glycosylation. Anti-hinge antibodies (AHAs) recognize immunoglobulin G (IgG) hinge neoepitopes exposed following cleavage by inflammation-associated proteases, and are also frequently observed in RA, and at higher levels compared to healthy controls (HCs). Here, we investigated AHA specificity and levels of Fab glycosylation as potential immunological markers for RA. Method: AHA serum levels, specificity, and Fab glycosylation were determined for the IgG1/4 -hinge cleaved by matrix metalloproteinase-3, cathepsin G, pepsin, or IdeS, using enzyme-linked immunosorbent assay and lectin affinity chromatography, in patients with early active RA (n = 69) and HCs (n = 97). Results: AHA reactivity was detected for all hinge neoepitopes in both RA patients and HCs. Reactivity against CatG-IgG1 -F(ab´)2 s and pepsin-IgG4 -F(ab´)2 s was more prevalent in RA. Moreover, all AHA responses showed increased Fab glycosylation levels in both RA patients and HCs. Conclusions: AHA responses are characterized by elevated levels of Fab glycosylation and highly specific neoepitope recognition, not just in RA patients but also in HCs. These results suggest that extensive Fab glycosylation may develop in response to an inflammatory proteolytic microenvironment, but is not restricted to RA.